Rethinking credit risk under the malinvestment concept: The case of Germany, Spain and Italy - Aykut Ekinci (European Financial and Accounting Journal, 2016)
This study argues that increasing malinvestment in an economy raises the actual credit risk but not the calculated credit risk until the onset of a recession. To this end, I analyse the relationship between credit risk and malinvestment in Germany, Spain, and Italy using a credit risk indicator based on nonfinancial corporate bond yields and annual loan growth for nonfinancial corporations from January 2004 to November 2014 on a monthly basis. The study also analyses Italy using sectorial non-performing loans data since Italy was the most affected by malinvestment among the countries in question. As a result, this paper suggests that banks should include malinvestment as a subcomponent of credit risk and recognize that the actual credit risk is higher than the calculated credit risk during artificial booms. This recommendation also underscores that malinvestment should be analysed more empirically.
Keywords: B53; E32; E50; 650; Austrian Business Cycle; Credit risk; Malinvestment; Monetary Transmission Mechanism